Serotonergic hallucinogens and recognition of facial emotion expressions: a systematic review of the literature - Juliana M. Rocha; Flávia L. Osório; José Alexandre S. Crippa; José Carlos Bouso; Giordano N. Rossi; Jaime E. C. Hallak; Rafael G. dos Santos (SAGE Publishing, 2019)
Background: Recognition of emotions in facial expressions (REFE) is a key aspect of social cognition. Anxiety and mood disorders are associated with deficits in REFE, and anxiolytics and antidepressants reverse these deficits. Recent studies have shown that serotonergic hallucinogens (i.e. ayahuasca, dimethyltryptamine, psilocybin, lysergic acid diethylamide [LSD], and mescaline) have anxiolytic and antidepressant properties, but their effects on REFE are not well understood. The purpose of the study was to conduct a systematic review analyzing the effects of serotonergic hallucinogens on REFE in humans. Methods: Studies published in the PubMed, PsycINFO, and Web of Science databases until 19 October 2018 which analyzed the effects of serotonergic hallucinogens on REFE in humans were included. Results: Of the 62 studies identified, 8 studies were included. Included studies involved the administration of a single or a few doses of LSD or psilocybin, and most trials were randomized and controlled with placebo. LSD and psilocybin reduced the recognition of negative emotions in most studies and modulated amygdala activity to these stimuli, which was correlated with antidepressive effects in patients. Both drugs were well tolerated. Conclusions: Serotonergic hallucinogens reduced the recognition of negative emotions by modulating amygdala activity. Despite the small sample sizes, results suggest that serotonergic hallucinogens show promising beneficial effects on deficits in REFE.